JEWELRY IN CELUK: ITS TRENDS, DEVELOPMENT, AND IMPLICATIONS FOR THE VILLAGE ARTISANS - I Ketut Sida Arsa; Ni Made Ary Widiastini (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2018)
This study was aimed at explaining jewelry production, its development and implications of the developing trends. This study was conducted in Celuk Village, Gianyar Regency, a place or arena of production, distribution and at the same time sale of jewelry in Bali, Indonesia, in which Celuk is regarded as the basis for jewelry. This paper explains the development of jewelry at the beginning of the emergence of tourism and the implications, and the introduction of casting machine as the method of production which had an implication in the change of human labor, in which the artisans became machine power regarded as more professional in jewelry production. The data of this ethnographic study were collected through observation, in-depth interview, library research, and internet search. The finding showed that the presence of jewelry that is developing in Celuk Village does not give an optimal positive contribution to the community of the village as artisans, but in stead, it gives profits to the people outside the village who are involved in the development of the jewelry trends. The entrance of tourism with the implication on the high level of jewelry production and sale in Celuk Village started from 1980s gave profits to tour guides who were regarded as the ones who deserve to get fee in a large amount by the artisans. When there was a trend in jewelry in 2010-2014, in which the demand for jewelry like accessories for kebaya cloth for going to the temple and a ring with gemstone drove away the artisans whose position had been replaced by casting machines and workers who came from outside of Celuk Village who were regarded more professional by jewelry business people in producing standard jewelry in a large quantity. In this paper it is understood that artisans in Celuk Village are not able to obtain an optimal use from jewelry trends that develop in their location due to various factors such as the low level of education of the artisans, low level of profesionalism in working, and the low level of ability of the artisans in production management